The Reformulation of Dakwah Science and its Parts - Syukriadi sambas (Al-Hikmah: Jurnal Dakwah dan Ilmu Komunikasi, 2005)
Nowadays Islamic Dakweh has existed as a part of Islamic Studies. But, t was not clear enough how this science was buit or structured.This article answers theproblems of Dakwah structure asa part of Islamic Sciences, from its ontologic,epistemologic and axiologic point of view "The tree ol Dakwah Science is a tree in Islamic Sciences park The writer divides Dakwah Science into two main parts, those are Dawah B Ahsan al-Qawl and Dawah Bi Ahsan al Amal, which are divided again into Irsyad Islam internalization and transmission), Tabligh Islam (transmission dan diffusion), Tadbir Islam (transformation institutionalization and management of Islamic Institution) Tathwir/Tamkin Islam (transformation empowering) This article could be as a bridge of formufton in Dakwah Science and its parts